Efficacy of bipolar release in neglected congenital muscular torticollis patients - Seyhan, Nevra; Jasharllari, Lorenc; Keskin, Mustafa; Savacı, Nedim (Springer, 2012)
Surgical correction of the congenital muscular torticollis (CMT) is recommended for patients with unsuccessful conservative treatment. The aim of this study is to evaluate the efficacy of surgical release of congenital muscular torticollis in neglected cases. We retrospectively evaluated the data of our patients in terms of age, sex, clinical presentation, localization of the lesion, diagnostic tests, and additional abnormalities. The age at operation ranged from 6 to 23 years. Complete muscular release as determined by pre-operative and postoperative range of motion measurements was achieved in all of the patients by bipolar release. In this study, neck motion and head tilt showed marked improvement with surgical treatment in cases with CMT who were admitted to the hospital lately. Congenital muscular torticollis patients can benefit from surgical intervention above the age of 5. Bipolar release is an adequate and complication-free method.
Keywords: Bipolar Release; Congenital Muscular Torticollis